2023
DOI: 10.1029/2023gl105525
|View full text |Cite
|
Sign up to set email alerts
|

The Asymmetric Predictive Power of Indian Ocean Dipole for Subsequent Year's ENSO: Role of Atlantic Ocean as an Intermediary

Lei Fan,
Xing Meng

Abstract: We examined the Indian Ocean Dipole (IOD)'s predictive ability for El Niño‐Southern Oscillation (ENSO). Our findings indicate that positive IODs have a stronger impact on the subsequent year's ENSO compared to negative IODs. To explain this asymmetry, we proposed the “IOD‐Atlantic‐Pacific” pathway, which involves the Atlantic in boreal winter as an intermediary. The pathway comprises two stages: (a) The asymmetric “IOD‐Atlantic” connection, where positive IODs in autumn trigger winter Atlantic Niño while negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Nevertheless, we found that model experimental results for El Niño (1991, 1994, 1997, 2009), La Niña (1998, 2000, 2016, 2017) and neutral (1990, 1993, 1996, 2013) years are similar (figures not shown). What remains unclear is the relative importance of the two tropical oceans and/or the Indian Ocean on the multi‐decadal modulations of this inter‐basin connection (Fan & Meng, 2023; Feng et al., 2023, 2024; Zhang & Han, 2021; Zhang & Li, 2023). This warrants a thorough investigation in future studies.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Nevertheless, we found that model experimental results for El Niño (1991, 1994, 1997, 2009), La Niña (1998, 2000, 2016, 2017) and neutral (1990, 1993, 1996, 2013) years are similar (figures not shown). What remains unclear is the relative importance of the two tropical oceans and/or the Indian Ocean on the multi‐decadal modulations of this inter‐basin connection (Fan & Meng, 2023; Feng et al., 2023, 2024; Zhang & Han, 2021; Zhang & Li, 2023). This warrants a thorough investigation in future studies.…”
Section: Conclusion and Discussionmentioning
confidence: 99%